Syntactic Anticipation and Arabic Reading Comprehension Among Hubulo Boarding School Students: Antisipasi Sintaksis dan Pemahaman Membaca Bahasa Arab di Kalangan Siswa Asrama Hubulo - Khairus Sakinah Chaeruddin; Hairuddin; Shahd Dibas (Language Development Center, 2026)
Background: Reading comprehension of unvocalized Arabic texts presents a significant challenge for students, as the absence of harakat requires readers to rely on grammatical and structural cues rather than phonological decoding to construct meaning. One cognitive mechanism believed to support this process is syntax cognitive anticipation defined in this study as the reader's ability to predict upcoming grammatical structures and sentence roles before fully encountering the text. Despite its theoretical relevance, the relationship between syntax cognitive anticipation and Arabic reading comprehension without diacritics remains underexplored, particularly within the Islamic boarding school context, where students are routinely exposed to unvocalized religious and classical texts. Purpose: This study aims to analyze the relationship between syntax cognitive anticipation ability and the understanding of Maharotul Qirā’ah among students of Hubulo Boarding School. Method: This study employed a quantitative correlational design to examine the relationship between syntax cognitive anticipation and Arabic reading comprehension without diacritics among students at Hubulo Islamic Boarding School. A sample of 60 students (N = 60) was selected from a population of 130 students using proportionate stratified random sampling. Data were collected through a syntax cognitive anticipation test and a reading comprehension test of unvocalized Arabic texts, and analyzed using Pearson product-moment correlation. Results and Discussion: The results revealed a moderate, statistically significant positive correlation between syntax cognitive anticipation and reading comprehension without diacritics, r(58) =534, p <001, N = 60, 95% CI [32,69]. Based on standard interpretation criteria for correlation coefficients, this value falls within the moderate range, indicating that students with stronger syntactic anticipation ability tend to demonstrate better comprehension of unvocalized texts, while syntax anticipation accounts for approximately 28.5% of the variance in comprehension scores (r² =285). Conclusion and Implications: This study concludes that syntactic cognitive anticipation ability plays an important role in improving students' comprehension of unvocalized maharotul qirā'ah, as demonstrated by a moderate and statistically significant positive correlation, r(58) =534, p <001, N= 60. The practical implication is that teachers need to incorporate syntactic structure anticipation exercises into Arabic language instruction to enhance students' ability to read unvocalized texts. Future research is recommended to expand the variables and learning contexts examined in order to obtain a more comprehensive understanding of the factors influencing Arabic reading comprehension.